Kajian Beberapa Jenis Pupuk dan Pestisida Organik Terhadap Pertumbuhan dan Hasil Tanaman Sawi di DKI Jakarta - Emi Sugiartini (Jurnal Penelitian Pertanian Terapan, 2014)
Until the current level of dependence on agricultural products in DKI-Jakarta from other areas increasing, estimated level of vegetable consumption / capita in urban -9.8 1.1% higher if compared to rural areas. Increased production and plant health conducted with crop rotation, intercropping, planting the right varieties, biological pest control. One of the environmentally-friendly technologies that can be used to improve the quantity and quality of the horticultural farming is very suitable for the conditions in Jakarta are the organic farming. The purpose of the study, assessing alternative technology packages organic farming leaf vegetable crops in the dry season, conducted from May to December 2008. This assessment activities carried out in Rawasari, Jakarta-Central, involving 6 farmer cooperators. As the indicator is a mustard plant. The design used was a randomized block design with 6 replications and 4 were tested technology package include: a) BPTP fertilizer (from urban waste)+Pest control with Nemasal (botanical pesticides), b) Fertilizer Dharmajaya (from beef cattle waste)+Pest control with sweeping (sweep with cloth), c) Fertilizer Pegadungan (from enceng gondok+stater)+Pest control with sweeping and d) Farmers fertilizer (chicken manure+Urea)+control OPT with Curacron/decis. The results of study of organic technology package on leaf vegetable crops (mustard) in DKI-Jakarta showed that, using fertilizer Dharmajaya (waste from the abattoir) with sweeping OPT can increase the growth and yield of mustard plants, equivalent if using fertilizer formulations BPTP (waste from urban waste + enrichmen). With the use of packet 1, it gives the highest profit, ie the B / C ratio: 3.8. While the B / C ratio is the lowest obtained in the use of packet 3, the gain B / C ratio is less than 1. It shows that, organic farming technologies provide considerable opportunities high in leaf vegetable farming, especially in the mustard plant in the dry season. Keywords: fertilizers, pesticides, growth and yield